Sucrose, Cobalt Chloride and Aerated Soft Drink Improves the Vase Life and Quality of Cut Scapes of Hemerocallis fulva - Arief, Z Mohmad; Tahir, Inayatullah (Journal of Postharvest Technology, 2015)
A study was conducted to examine the post-harvest characteristics of cut scapes of Hemerocallis fulva cv. Royal Crown. The scapes were harvested at 0900 hrs., one day before anthesis of the first bud. The scapes were held in following test solutions: Soft Drink (25%); Soft Drink (25%) + Sucrose (0.15M) and Soft Drink (25%) + Sucrose (0.15M) + CoCl2 (0.2mM). Distilled water alone served as control. Soft Drink (25%) +Sucrose (0.15M) significantly prolonged the vase life of scapes by six days as compared to control. Besides significantly increasing the number of blooms per scape, larger flower diameter was maintained in this treatment. The total acetone extractable pigment content of the perianth tissue of scapes held in this treatment was almost doubled as compared to control. When CoCl2 (0.2mM) was added to this test solution containing Soft Drink (25%) + Sucrose (0.15M), the effects were much more pronounced and the solution uptake was significantly promoted. The present results suggest that Soft Drink (Limca) in combination with Sucrose (0.15M) + CoCl2 (0.2mM) can serve as an effective vase solution for the enhancement of vase life and postharvest quality of the cut flowers of Hemerocallis fulva.